Analysis of Simile Translation from English to Indonesian in The Silent Patient (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Analysis of Simile Translation from English to Indonesian in The Silent Patient This study analyzes what translation strategies are used in translating similes in English into Indonesian in the novel The Silent Patient by Alex Michaelides. The theory of simile translation strategies based on Pierini are used as the theoretical framework of this research. In addition, this research uses qualitative research and the data were classified by identifying and analyzing the strategies used to translate the similes in the source text based on Pierini’s theory. The result of this study shows that all of the strategies that have been used to translate the simile identified in the novel and the dominant strategy used is literal translation (retention of the same vehicle) 87.10% by translator to translate the simile in the novel.